Nonlinear and synergistic effects of demographic characteristics on urban polycentric structure using SHAP - Yichen Ruan; Xiaoyi Zhang; Mingyu Zhang; Feiyang Sun; Qiuxiao Chen (Scientific Reports)
Abstract Polycentric urban development is promoted by urban planners and policy makers for its perceived benefits of alleviating urban issues. Theoretically, a polycentric urban structure is formed when different demographic groups present a collection of diverse and unique housing location preferences. Yet, only limited empirical studies have fully captured the complex effects of demographic characteristics on urban polycentric structures. Our study utilizes detailed demographic data and employs interpretable machine learning models to elucidate the nonlinear and synergistic relationship between demographic characteristics and the urban polycentric structure in the context of a city of 10 million population in China. When characterizing urban centers, the three most important demographic groups are young females, senior married couples, and middle-aged single individuals with basic education. Each urban center presents distinctive demographic compositions; for instance, middle-aged married individuals exerting a stronger influence in certain contexts, whereas in senior resident groups, married individuals have a more pronounced impact. Spatial heterogeneity is observed in the demographic profiles of urban centers; for instance, primary central cores are predominantly young, single females, whereas peripheral and secondary centers have stronger presence of highly educated residents.